Strain-engineered diffusive atomic switching in two-dimensional crystals - Janne Kalikka (Nature Portfolio, 2016)
Strain engineering allows design of materials with tailored properties. Here, the authors show that strain can be used to control atomic diffusion in Sb2Te3-GeTe superlattices, and they propose general design rules to enable atomic switching functionalities in van der Waals heterostructures.